ANALISIS EPIC KEPEMIRSAAN ”FILM DOKUMENTER PERAHU JONG” SEBAGAI MEDIA PROMOSI BUDAYA - Evaliata Br Sembiring; Riki Riki; Afdhol Dzikri (Politeknik Negeri Bali, 2019)
Jong Boat is one form of Melayu culture of a unique game in Riau Islands. Preservation of the game is done through the race so it has the potential to increase local and foreign tourist visits, especially in the Riau Islands. Therefore, documentation is required in the form of documentary film as well as can be used as a medioum for dissemination of information or promotion for the public. Documentary film produced through the film production process of the Perahu Jong at once documenting the activities of the race in 2017 by using Luther-Sutopo method, so that the production stage is done systematically and programmed. Continued from production actiivities is film analysus that is used as a cultural promotion medium using the EPIC Model approach. The results of the analysis are: (1) The content of the documentary film is in accordance with the original so as to strengthen the empathy and persuasion of someone to know about the Perahu Jong; (2) The impact felt by the audience is more enthusiastic to join the race; (3) The community’s knowledge of Perahu Jong is increasing because the communication messages applied to the film are packed in detail and simple; (4) Based on EPIC model analyzed from empathy, persuasion, impact and communication on documentary of Perahu Jong, it can be concluded that documentary should be used as media of cultural promotion